Perilaku Pekerja Laundry Terhadap Penggunaan Alat Pelindung Diri Tahun 2022: (Studi kasus di RS X Sidoarjo) - Desysaputri, Vera; Suryono, Hadi; Suprijandani; Nurmayanti, Demes; Marlik (Jurnal Higiene Sanitasi, 2023)
Personal protective equipment (APD) is a tool that has a function to protect humans in the threat of contaminants caused by a job that has a potential risk of danger. This study aims to determine the behavior of using APD in the Laundry at X Hospital, Sidoarjo. This research method was descriptive through a cross sectional approach. The research variables were worker behavior related to knowledge, attitudes, facilities and infrastructure and supervision of the use of APD. The population of this study were 8 respondents from all workers in the Laundry. Determination of the sample of this study was total sampling technique. The data collection tools used in this study were questionnaires and observations. Data analysis was done descriptively. The results of the study showed that 87.5% of laundry good knowledge, 100% good attitude, 84% good infrastructure facilities, and 82% good supervision. Overall, the behavior of laundry was said to be well behaved. The conclusion of this study was the behavior of using APD for laundry is said to be well behaved. It is recommended to apply strict sanctions/punishments to laundry who do not use APD and tightened supervision to increase worker awareness in complying with regulations on the use of APD.